Compilation of longitudinal microbiota data and hospitalome from hematopoietic cell transplantation patients - Liao, Chen; Taylor, Bradford P.; Ceccarani, Camilla; Fontana, Emily; Amoretti, Luigi A.; Wright, Roberta J.; Gomes, Antonio L. C.; Peled, Jonathan U.; Taur, Ying; Perales, Miguel-Angel; van den Brink, Marcel R. M.; Littmann, Eric; et al. (Scientific data, 2021)
The impact of the gut microbiota in human health is affected by several factors including its composition, drug administrations, therapeutic interventions and underlying diseases. Unfortunately, many human microbiota datasets available publicly were collected to study the impact of single variables, and typically consist of outpatients in cross-sectional studies, have small sample numbers and/or lack metadata to account for confounders. These limitations can complicate reusing the data for questions outside their original focus. Here, we provide comprehensive longitudinal patient dataset that overcomes those limitations: a collection of fecal microbiota compositions (>10,000 microbiota samples from >1,000 patients) and a rich description of the “hospitalome” experienced by the hosts, i.e., their drug exposures and other metadata from patients with cancer, hospitalized to receive allogeneic hematopoietic cell transplantation (allo-HCT) at a large cancer center in the United States. We present five examples of how to apply these data to address clinical and scientific questions on host-associated microbial communities. Measurement(s) gut microbiome measurement • Cell Density • Clinical Data Technology Type(s) DNA sequencing • quantitative PCR • clinical laboratory measurement • 16s ribosomal gene sequencing assay Factor Type(s) relative abundance of bacteria • timepoint of hematopoietic cell transplantation • type of hematologic malignancy • time and route of drug administration • type of bacterial infection Sample Characteristic - Organism Homo sapiens Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13584986